A Continuous Observation Workflow Time Study to Assess Intravenous Push Waste. (October 2021) - Hertig, John; Jarrell, Kaitlyn; Arora, Prachi; Nwabueze, Jonell; Moureaud, Charlotte; Degnan, Daniel D.; Trujillo, Tate
Background: There are significant costs associated with proper controlled substance disposal, management, and regulatory compliance. Given the high abuse potential of fentanyl, hydromorphone, and morphine it is imperative that (1) product waste is minimized; and (2) waste procedures are followed to ensure safe disposal. Research is needed to better understand the financial and workforce impacts of drug waste on inpatient hospital units. The primary objective of this study was to quantify the waste associated with administering fentanyl, hydromorphone, and morphine via the intravenous push route. Two categories of waste were evaluated: (1) the quantity (mg/µg) of drug disposed; and (2) workforce time associated with the waste disposal process.Methods: A workflow time study design, a sub-set of continuous direct observation time motion studies, was employed to achieve the research objectives. A data collection tool was developed to capture medication type, waste amount, activity time stamps, total time, and number of interruptions at two separate study sites. Descriptive statistics were conducted on all the data measures. The number of assessments, total values, and mean values were reported for each drug (fentanyl, hydromorphone, and morphine) separately as well as grouped data.Results: A total of 669 distinct waste observations meeting inclusion criteria were collected during a study period of 15 days. In total, 207 mg of hydromorphone and 17 962.50 µg of fentanyl were wasted during this study. Nursing staff time associated with the wasting process totaled 50 990 seconds (849.83 minutes or 14.16 hours). A combined waste (loss) of approximately 1605.39 was associated with controlled substance wasting. The cost per dose wasted in this study was found to be 2.40 for all medications. When a yearly extrapolation model was applied to the four study units, the total combined product and workforce waste cost was 35 425.Conclusion: There are financially significant costs associated with wasting both the product and the valuable time of a skilled workforce. Optimizing product size, taking special note to match product availability with common practice use, would reduce the associated financial burden on our health-systems nationwide.